Clearing the forest, adding social struggles: territorialities and alternatives in the Argentinian environmental disaster - Joaquin Ulises Deon (Íconos)
This article explores the several collective narratives developed by participants of the social and environmental struggles, in response to the many ecological disasters that plagued Argentina in the last decade. These adversities have resulted in around 95.000 persons being displaced during the same period. Quantitative data was gathered by means of an active participant observation methodology. Additionally, legislation and social media posts were also inspected. The present study provides evidence that the advance of colonialist development plans has resulted in a sustained clearing of forests, fumigation and extermination of minority peoples and social groups. The actions of the powerful power networks behind these current colonialist practices are visualized and the high environmental impact of their territorialization practices is illuminated (particularly in the province of Cordoba). Resistance against the above process in the Gran Chaco and Espinal ecoregions is researched as a case of emancipatory social action. Likewise, it becomes evident how the State has criminalized these struggles in its attempts to break down the social coalitions built by the assemblies and social movements, involved in building a collective counter hegemony. Finally, the conclusion is reached that the defense of forests and life, as driven by the socio environmental assemblies is progressively uprooting agribusiness, large scale metallic mining, quarries and real estate development.